MXene / h-MoO3 electrode material for zinc ion battery as well as preparation method and application of MXene / h-MoO3 electrode material

By preparing MXene/h-MoO3 composite materials, the problems of high preparation cost and poor stability of zinc ion batteries are solved, and higher electrochemical performance and cycle stability are achieved. It is suitable for zinc ion batteries and other energy storage devices.

CN119230790AActive Publication Date: 2024-12-31DALIAN POLYTECHNIC UNIVERSITY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411502842.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The problems of high preparation cost of zinc ion batteries, difficult to control the microscopic morphology of electrode materials and poor stability, affecting their performance and application potential.

Method used

Using MXene/h-MoO3 composite material as electrode material, ultra-thin Ti3C2Tx nanosheets were prepared by etching titanium carbide by hydrochloric acid and lithium fluoride, and ultrasonic stirring with mixed solution of ammonium molybdate and formic acid to prepare excellent conductivity, MXene/h-MoO3 composite material with excellent electrochemical performance and strong stability.

Benefits of technology

It significantly reduces the preparation cost of zinc ion batteries, improves the overall performance and cyclic stability of electrode materials, provides higher specific capacitance and electrochemical reaction activities, and meets the goals of green environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005103040350000011
    Figure HDA0005103040350000011
  • Figure HDA0005103040350000012
    Figure HDA0005103040350000012
  • Figure HDA0005103040350000021
    Figure HDA0005103040350000021
Patent Text Reader

Abstract

The invention relates to the field of electrochemistry, in particular to an MXene / h-MoO3 electrode material for a zinc ion battery as well as a preparation method and application of the MXene / h-MoO3 electrode material. The preparation method comprises the following steps: preparing a Ti < 3 > C < 2 > T < x > MXene material; the prepared liquid MXene is dropped into a mixed solution of ammonium molybdate and formic acid, ultrasonic stirring is performed to obtain a uniform solution, centrifuged solids are washed with deionized water for multiple times, and MXene / h-MoO3 is obtained after drying. The MXene / h-MoO3 composite material adopts MXene as a framework, has more active sites and is applied to the zinc ion battery to remarkably improve the electrochemical performance of the zinc ion battery, the prepared MXene / h-MoO3 composite material combines the advantages of MXene and h-MoO3 and is good in conductivity, excellent in electrochemical performance and high in overall stability, the preparation process is simple and safe, and the preparation method is suitable for industrial production. And the material is expected to be widely applied to electrode materials of zinc ion batteries and even other energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemistry, and in particular to a MXene / h-MoO2 composite for zinc ion batteries. 3 Electrode materials, preparation methods and applications thereof. Background Art

[0002] Zinc-ion batteries are a new type of rechargeable battery based on the storage and release of zinc ions. Compared with traditional lithium-ion batteries, zinc-ion batteries have higher energy density, lower cost and better safety performance. Zinc-ion batteries have many significant advantages. Zinc materials are relatively cheap and abundant, so the manufacturing cost of zinc-ion batteries is low. Secondly, zinc-ion batteries have higher energy density and can provide longer battery life. In addition, zinc-ion batteries have better safety performance and are not prone to overheating or fire. Zinc ions have potential applications in many fields. First, it can be used as a battery for portable electronic devices, electric vehicles and energy storage systems. Since zinc-ion batteries have lower cost and higher energy density, they can provide longer service life and higher performance. Secondly, zinc-ion batteries can be used for the storage of renewable energy. Zinc-ion batteries can store solar and wind energy and release it when needed, thereby balancing power supply and demand. In addition, zinc-ion batteries can also be used in special applications such as emergency power supplies and wireless sensor networks. However, zinc-ion batteries also have some challenges and problems, such as high preparation cost, difficult to control the micromorphology of electrode materials, and poor stability. Further research and development are needed to improve the performance and stability of zinc-ion batteries. Summary of the invention

[0003] The present invention provides a MXene / h-MoO for zinc ion batteries 3 Electrode material and its preparation method and application. The present invention first uses hydrochloric acid and lithium fluoride to etch titanium aluminum carbide to obtain ultra-thin Ti 3 C 2 T x Nanosheets, and then prepare MXene / h-MoO 3 Composite materials, prepared MXene / h-MoO 3 Composites combining MXene and h-MoO 3 The advantages of the composite material are good in conductivity, excellent in electrochemical performance, strong in overall stability, simple in preparation process, low in energy consumption, and safer in process. The present invention provides a new idea and method for producing MXene-based electrode materials with good electrical properties, which is expected to be widely used in electrode materials for zinc ion batteries and even other energy storage devices.

[0004] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0005] The present invention provides a MXene / h-MoO for zinc ion batteries 3 The method for preparing the electrode material comprises the following steps:

[0006] (1) Preparation of Ti 3 C 2 T x MXene materials;

[0007] (2) Preparation of MXene / h-MoO 3 Material:

[0008] The liquid MXene prepared in step (1) was dropped into a mixed solution of ammonium molybdate and formic acid, and ultrasonic stirring was performed to obtain a uniform solution. The solid after centrifugation was washed with deionized water for multiple times and dried to obtain MXene / h-MoO 3 .

[0009] In the above technical solution, further, the mass ratio of the MXene, ammonium molybdate and formic acid is 0.5-1.5:1:1-1.2.

[0010] In the above technical solution, further, step (1) prepares Ti 3 C 2 T x The method of MXene material is as follows: dissolve lithium fluoride in hydrochloric acid solution, stir, add titanium aluminum carbide, stir in a water bath; centrifuge, wash with hydrochloric acid and then continue to wash with deionized water, then ultrasonically ice water bath for 1 hour, and continue to centrifuge to obtain ultrathin Ti 3 C 2 T x Nanosheets.

[0011] In the above technical solution, further, the mass ratio of the titanium aluminum carbide, lithium fluoride and hydrochloric acid is 5:6-10:110-120; the concentration of the hydrochloric acid solution is 11-13 mol L -1 .

[0012] In the above technical solution, further, the water bath stirring temperature is 40-50° C.; the water bath stirring time is 46-50 h; and the ultrasonic ice water bath time is 0.8-1.2 h.

[0013] In the above technical solution, further, the centrifuge speed is 3500-4000 rpm; the pH of the solution after washing with deionized water is 6-7.

[0014] In the above technical solution, further, in the step (2), the ultrasonic stirring time is 0.8 to 1.2 hours, and the ultrasonic reaction temperature is 50 to 70°C.

[0015] In the above technical solution, further, in the step (2), the centrifuge speed is 3500-4000 rpm; and the drying temperature is 60-80°C.

[0016] The present invention also provides a MXene / h-MoO 3 The electrode material is characterized in that it is prepared by any one of the above methods.

[0017] The present invention also provides the aforementioned MXene / h-MoO 3 Application of electrode materials in zinc-ion batteries.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention uses MXene as a precursor, which has a wide range of raw material sources and low cost. Its application in zinc-ion batteries can significantly reduce the preparation cost, which is in line with the long-term goals of green environmental protection and sustainable development. At the same time, MXene has a porous structure, and the prepared MXene contains abundant macropores, mesopores and micropores, with a large specific surface area. Therefore, compared with other two-dimensional materials, the overall performance of the electrode material prepared by MXene is relatively excellent.

[0020] (2) The present invention prepares MXene / h-MoO 3 Composite materials have simple methods, low energy consumption, and are easy to control microstructure, particle size distribution and dispersibility.

[0021] (3) MXene / h-MoO prepared by the present invention 3 The composite material combines the advantages of high specific capacitance of transition metal compounds and excellent conductivity of MXene. 3 It can significantly improve the stacking of MXene nanolayers, effectively improve their microstructure, and help improve the electrochemical performance and cycle stability of composite electrode materials. 3 Provide pseudocapacitance, good electrochemical reaction activity, high specific capacitance, h-MoO 3 Combining it with MXene can fully combine the advantages of both. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The MXene / h-MoO prepared in Example 1 3 X-ray diffraction patterns of the composite materials as electrode materials.

[0023] Figure 2 The MXene / h-MoO prepared in Example 1 3 Scanning electron microscopy images of the composite material as electrode material.

[0024] Figure 3 The MXene / h-MoO prepared in Example 1 3 As electrode material in 2 mol·L -1 Zn(OTF) 2 Cyclic voltammograms at different scan rates in electrolyte.

[0025] Figure 4 The MXene / h-MoO prepared in Example 1 3 The composite material was used as an electrode material at 2 mol·L -1 Zn(OTF) 2 Constant current charge and discharge curves at different current densities in the electrolyte.

[0026] Figure 5 The MXene / h-MoO prepared in Example 1 3 The composite material was used as an electrode material at 2 mol·L -1 Zn(OTF) 2 AC impedance diagram in electrolyte.

[0027] Figure 6 The MXene / h-MoO prepared in Example 1 3 The composite material was used as an electrode material at 2 mol·L -1 Zn(OTF) 2 Cycling performance and Coulombic efficiency of the devices in electrolyte after 1000 cycles. DETAILED DESCRIPTION

[0028] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0029] If no specific experimental steps or conditions are specified in the examples, all the experiments were carried out according to the conventional experimental steps or conditions described in the literature in the field. The reagents or instruments used without specifying the manufacturer are all conventional reagents that can be obtained commercially.

[0030] In order to more intuitively disclose the technical solution of the present invention and highlight the beneficial effects of the present invention, the present invention is now described in combination with specific embodiments. 3 The electrochemical properties are described.

[0031] Example 1

[0032] Preparation of MXene / h-MoO3 Sample material, including the following steps:

[0033] (1) Preparation of MXene material: 1.6 g of lithium fluoride and 20 ml of 12 M hydrochloric acid were taken, stirred for 15 min, 1 g of titanium aluminum carbide was added, and stirred in a water bath at 45 ° C for 48 h; after the above stirring, the sample was centrifuged at 4000 rpm, washed with 2 M hydrochloric acid and then continued to be washed with deionized water until neutral; after washing, the obtained sample was ultrasonically treated in an ice water bath for 1 h; the above sample was centrifuged for 1 h to obtain a liquid ultrathin Ti 3 C 2 T x Nanosheets;

[0034] (2) Preparation of MXene / h-MoO 3 :The liquid MXene obtained in the above steps was dripped into the mixed solution of ammonium molybdate and formic acid with a rubber-tipped dropper. According to 100 mg of MXene, 100 mg of ammonium molybdate and 100 mg of formic acid, ultrasonic stirring was performed at 60 ° C for 1 h to obtain a uniform solution. The solid after centrifugation was washed with deionized water several times and dried at 80 ° C to obtain MXene / h-MoO 3 sample.

[0035] MXene / h-MoO for Zn-ion batteries 3 The electrode preparation method comprises:

[0036] (1) Process the current collector and cut the conductive substrate nickel foam into 1 cm 2 shape, and then acetone, 3 mol L -1 The samples were ultrasonically cleaned with hydrochloric acid, anhydrous ethanol and deionized water for 15 min and finally dried at 60 °C for 12 h for later use.

[0037] (2) Active materials (MXene / h-MoO 3 ), conductive agent (acetylene black) and binder (polytetrafluoroethylene concentrated solution (10wt%)), are mixed with anhydrous ethanol to form a uniform solid, coated on a clean and dry nickel foam (the coating amount of active material is generally about 3mg), and then vacuum dried at 60℃ for 12h, and then pressed into a sheet at 10MPa to obtain a working electrode.

[0038] The material prepared by the method of Example 1 was tested and electrochemically tested, and the results are shown in the attached drawings; at the same time, the results of the electrochemical performance of the following examples and comparative examples are shown in Table 1.

[0039] in, Figure 1 The MXene / h-MoO prepared in Example 1 3The X-ray diffraction pattern of h-MoO 3 ), the test results show obvious h-MoO 3 Diffraction peaks indicate that MXene / h-MoO was successfully synthesized 3 Composite materials.

[0040] Figure 2 The MXene / h-MoO prepared in Example 1 3 The SEM images show that MXene exhibits a rich three-dimensional hierarchical porous structure with irregularly aggregated h-MoO 3 Nanoparticles are randomly arranged and distributed on the surface and inside of MXene, and MXene serves as a substrate to support h-MoO 3 At the same time, h-MoO 3 It can also prevent MXene from self-stacking behavior. The electrolyte can easily diffuse in the stabilized MXene, which significantly improves the electrochemical performance.

[0041] Figure 3 The MXene / h-MoO prepared in Example 1 3 The cyclic voltammograms at different scan rates show that the curves exhibit obvious redox peaks with increasing scan rate, indicating good electrochemical performance.

[0042] Figure 4 The MXene / h-MoO prepared in Example 1 3 In the charge and discharge spectra at different scanning current densities, all curves show approximately symmetrical characteristic shapes, indicating that the electrode has excellent reversibility and good Coulombic efficiency.

[0043] Figure 5 The MXene / h-MoO prepared in Example 1 3 The AC impedance spectrum shows that the charge transfer resistance of the composite material is very small, indicating that the electronic charge transfer process is relatively fast.

[0044] Figure 6 The MXene / h-MoO prepared in Example 1 3 The composite material was used as an electrode material at 2 mol·L -1 Zn(OTF) 2 Cycling performance and Coulombic efficiency of the device in electrolyte after 1000 cycles. The device shows excellent cycling stability with a capacitance retention of 96.08%. The corresponding Coulombic efficiency is calculated to be around 99%, indicating that the device has good reversibility.

[0045] Example 2

[0046] The only difference from Example 1 is that 120 mg of MXene, 80 mg of ammonium molybdate, and 80 mg of formic acid are mixed, and the rest is the same as Example 1.

[0047] Example 3

[0048] The only difference from Example 1 is that 80 mg of MXene, 120 mg of ammonium molybdate, and 120 mg of formic acid are mixed, and the rest is the same as Example 1.

[0049] Comparative Example 1

[0050] In this comparative example, commercial polystyrene and h-MoO 3 The preparation steps of the compound are as follows:

[0051] 100 mg of polystyrene, 100 mg of ammonium molybdate, and 100 mg of formic acid were mixed according to the mass ratio, and ultrasonic stirring was performed to obtain a uniform solution. The solid after centrifugation was washed with deionized water for several times and dried to obtain polystyrene / h-MoO 3 sample.

[0052] A polystyrene / h-MoO2 for zinc ion batteries 3 A method for preparing a finished electrode, comprising:

[0053] (1) The preparation process is the same as in Example 1.

[0054] (2) The active material is polystyrene / h-MoO 3 , the other preparation processes are the same as those in Example 1.

[0055] Comparative Example 2

[0056] In this comparative example, commercial V 2 O 5 with h-MoO 3 complex.

[0057] By mass ratio V 2 O 5 100 mg of ammonium molybdate, 100 mg of formic acid, and 100 mg of formic acid were mixed and ultrasonically stirred for 1 h to obtain a uniform solution. The solid after centrifugation was washed several times with deionized water and dried to obtain polystyrene / h-MoO 3 sample.

[0058] A V for zinc ion battery 2 O 5 / h-MoO 3 An electrode preparation method comprising:

[0059] (1) The preparation process is the same as in Example 1.

[0060] (2) The active substance is V 2 O5 / h-MoO 3 , the other preparation processes are the same as those in Example 1.

[0061] Comparative Example 3

[0062] This comparative example prepares MXene / 2D bismuth sample material, and the preparation method is as follows:

[0063] (1) Prepare MXene material, and its preparation process is the same as that in Example 1.

[0064] (2) Preparation of MXene / 2D bismuth: 0.1 mol C 10 H 14 N 2 Na 2 O 8 ·2H 2 O and 0.05mol Bi(NO 3 ) 3 ·5H 2 O, and added to 40mL deionized water; ultrasonic treatment for 1h, rinsed with deionized water and ethanol and dried in a vacuum oven at 60℃ for 6h. Then 0.05mol MXene was dropped into the above product, 40mL deionized water was added, and ultrasonic treatment was performed for 30min to obtain a uniformly mixed solution. The solid after centrifugation was washed with deionized water several times and dried to obtain a MXene / 2D bismuth sample.

[0065] A method for preparing a finished electrode of MXene / 2D bismuth for a zinc ion battery, comprising:

[0066] (1) The preparation process is the same as in Example 1.

[0067] (2) The active material is MXene / 2D bismuth, and the other preparation processes are the same as those in Example 1.

[0068] Comparative Example 4

[0069] This comparative example prepares MXene / graphene oxide, and the preparation method is as follows:

[0070] (1) Preparation of graphene oxide: 2 g of graphene raw material was placed in a 500 mL beaker, 35 mL of concentrated sulfuric acid (concentration of 98%) was added to the beaker, and stirred for 2 h; 8 g of potassium permanganate (analytical grade) was weighed and then slowly added to the above mixed solution while stirring. After the reaction, the beaker was placed in a 35°C constant temperature water bath for 6 h, 100 mL of deionized water was added, and stirring was continued for 30 min, and then 20 mL of 30% hydrogen peroxide was added and stirred for 30 min. Finally, 30 mL of concentrated hydrochloric acid and 200 mL of deionized water were added and stirred for 30 min to remove residual substances in the solution; the mixture was washed with deionized water until neutral, and the washed precipitate was placed in a refrigerator to freeze and agglomerate, and then freeze-dried for 24 h to obtain graphene oxide powder.

[0071] (2) Preparation of MXene / graphene oxide: The materials obtained in the above steps were mixed in a mass ratio of 100 mg MXene and 100 mg graphene oxide, and ultrasonically stirred for 1 h to obtain a uniform solution. The solid after centrifugation was washed with deionized water for multiple times and dried to obtain a MXene / graphene oxide sample.

[0072] A method for preparing a finished electrode of MXene / graphene oxide for a supercapacitor, comprising:

[0073] (1) The preparation process is the same as in Example 1.

[0074] (2) The active material is MXene / graphene oxide, and the other preparation processes are the same as those in Example 1.

[0075] The electrochemical performances of the above examples and comparative examples are shown in Table 1. From the results in Table 1, it can be seen that the prepared MXene / h-MoO 3 (Example 1) has a higher specific capacitance and excellent electrochemical performance. This is mainly due to the h-MoO 3 The addition of can provide a larger specific surface area, can significantly improve the situation that MXene is easy to self-stacking, and is beneficial to improving the electrochemical performance of composite electrode materials. In addition, alkali metal oxides have more energy storage active sites during the electrochemical energy storage process, and also provide more transmission channels for the transfer of electrons. Therefore, alkali metal oxides often have higher specific capacity than other metal oxides. The method involved in the present invention has a simple preparation process, low energy consumption, and a safer process. Since the synthesis of MXene nanosheets, this new two-dimensional material has become a huge demand in many research fields due to its large specific surface area, good surface chemical properties, good hydrophilicity and excellent electrical conductivity. In addition, the change in the amount of MXene added in Examples 2 and 3 affects the specific capacitance, but still has excellent electrochemical performance within a relatively high range.

[0076] Table 1 Electrochemical performance list of Example 1 to Comparative Example 4

[0077] Electrode Materials Electrolyte Specific capacitance (F / g) Example 1 <![CDATA[MXene / h-MoO 3 ]]> <![CDATA[2M Zn(OTF) 2 ]]> 395 Example 2 <![CDATA[MXene / h-MoO 3 ]]> <![CDATA[2M Zn(OTF) 2 ]]> 352 Example 3 <![CDATA[MXene / h-MoO 3 ]]> <![CDATA[2M Zn(OTF) 2 ]]> 329 Comparative Example 1 <![CDATA[Polystyrene / h-MoO 3 > <![CDATA[2M ZnSO 4 +0.1M MnSO 4 ]]> 280 Comparative Example 2 <![CDATA[V 2 O 5 / h-MoO 3 ]]> <![CDATA[2M Zn(OTF) 2 ]]> 275 Comparative Example 3 MXene / 2D Bismuth <![CDATA[2M ZnSO 4 ]]> 178 Comparative Example 4 MXene / graphene oxide <![CDATA[3M H 2 SO 4 ]]> 220

[0078] Those skilled in the art will appreciate that various modifications and variations may be made to the present invention without departing from the spirit or scope of the present invention. Therefore, if any modification or variation falls within the scope of protection of the appended claims and equivalents, it is considered that the present invention covers these modifications and variations.

Claims

1. A method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery, characterized in that: The steps include: (1) Preparation of Ti3C2T x MXene materials; (2) Preparation of MXene / h-MoO3 materials: Liquid MXene was dropped into a mixed solution of ammonium molybdate and formic acid, and ultrasonic stirring was performed to obtain a uniform solution. The solid after centrifugation was washed several times with deionized water and dried to obtain MXene / h-MoO3.

2. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 1, characterized in that: The mass ratio of the MXene, ammonium molybdate and formic acid is 0.5-1.5:1:1-1.

2.

3. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 1, characterized in that: Step (1) Preparation of Ti3C2T x The method of MXene material is as follows: dissolve lithium fluoride in hydrochloric acid solution, add titanium aluminum carbide, stir in a water bath, centrifuge, wash with hydrochloric acid and then continue to wash with deionized water, then ultrasonically ice water bath for 1 hour, and continue to centrifuge to obtain ultrathin Ti3C2T x Nanosheets.

4. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 3, characterized in that: The mass ratio of titanium aluminum carbide, lithium fluoride and hydrochloric acid is 5:6-10:110-120; the concentration of the hydrochloric acid solution is 11-13 mol L -1 .

5. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 3, characterized in that: The water bath stirring temperature is 40-50° C.; the water bath stirring time is 46-50 h; and the ultrasonic ice water bath time is 0.8-1.2 h.

6. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 3, characterized in that: The rotation speed of the centrifuge is 3500-4000 rpm; the pH value of the solution after washing with deionized water is 6-7.

7. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 1, characterized in that: In the step (2), the ultrasonic stirring time is 0.8 to 1.2 hours, and the ultrasonic reaction temperature is 50 to 70°C.

8. The method for preparing a MXene / h-MoO3 electrode material for a zinc ion battery according to claim 1, characterized in that: In the step (2), the centrifuge speed is 3500-4000 rpm; and the drying temperature is 60-80°C.

9. A MXene / h-MoO3 electrode material, characterized in that: The invention is prepared by any one of the methods of claims 1 to 8.

10. Use of the MXene / h-MoO3 electrode material according to claim 9 in zinc ion batteries.

Citation Information

Patent Citations

  • MoO3 composite carbon-dot lithium-ion battery anode material and preparation method thereof

    CN109301231A

  • Water-based zinc ion battery negative electrode, preparation method thereof and battery

    CN111509218A

  • Cobalt molybdenum sulfide loaded MXene material and preparation method thereof

    CN112072081A

  • Preparation method of MXene / zinc oxide / graphene composite material

    CN114864297A

  • Preparation method of MXene-based electrode material

    CN117316655A